Combination of MOORA and WASPAS Methods in Selecting the Best Hafidzoh - Dewi Maharani (International Journal of Basic and Applied Science, 2021)
The combination of the Multi-Objective Optimization method on the basis of Ratio Analysis (MOORA) and the Weight Aggregated Sum Product Assessment (WASPAS) is used by researchers in selecting the best hafidzoh so as to produce effective and efficient research objectives and make it easier for leaders to determine the best hafidzoh. Choosing the best hafidzoh is not an easy matter due to the large number of students and the large number of criteria given. Furthermore, the best students or candidates for hafidzoh are called alternatives, while the things that are assessed are called criteria. Based on the results of interviews and references that the researchers conducted, the criteria for helping the Chairperson of the Dzunnur'ain Simalungun Institute in determining the best hafidzoh were letter makhorijul, tajwid, itqon hifzd, adabul qiroah and Arabic. Meanwhile, the best alternative or candidate for hafidzoh is the total number of students in Lambaga Dzunnur 'ain, which is 30 students. Furthermore, researchers conducted analysis and calculations based on the formula of the MOORA method and the formula of the WASPAS method. The results of the analysis and calculations are that the Moora and WASPAS methods get the same best santri, namely the alternative name Santri 7, while for the second rank the alternatives obtained are santri 16 and santri 25.